Response of the human T-cell leukemia virus type 1 long terminal repeat to cyclic AMP. - Poteat, H T (1989)
The sequences that control transcriptional initiation of the provirus of the human T-cell leukemia virus type 1 (HTLV-1) are shown to be responsive to intracellular levels of cyclic AMP. A heptanucleotide sequence present within the 21-nucleotide repeat sequence that is similar to the cyclic AMP-responsive consensus (CRE) sequence was required for cyclic AMP-mediated increase in gene expression. Although the CRE-like sequences were contained within sequences that were responsive to the virally encoded trans-activator (tax), the evidence presented indicates that the mechanisms of promoter induction by the tax product and cyclic AMP are independent. The implication of cyclic AMP stimulation of HTLV-1 provirus gene expression for long-term persistence of infected T cells and for virus-induced transformation is discussed.